Study of excavated clays with kaolinite and dickite as pozzolanic materials - Hernan Yanguatin; Alejandra Tironi; Jorge Iván Tobón (Dyna, 2022)
In the present study, samples of excavated waste clays were thermally activated at 550 °C and 650 °C, these clays with low kaolinite content and presence of dickite have a limited industrial exploitation but are widely availability in developing countries and have the potential to use as pozzolanic material. The effects on the calcium hydroxide fixation and the compressive strength were evaluated in lime pastes and mortars blended with calcined excavated clays. The experimental results and statistical modelling using multiple regression analysis showed that the compressive strength at 28 days increased 5%, when the kaolinite increased up to 20% and dickite up to 40%, for a clay with SSA of 4000 cm2/g and calcined at 550 °C. Also, by increasing SSA up to 6000 cm2/g and calcination temperature up to 650 °C, the compressive strength increased 10% and 15%, respectively.